2, 4‐D and 2, 4‐D butoxyethyl ester behavior in Eurasian and hybrid watermilfoil (Myriophyllum spp.). Issue 2 (23rd October 2021) - Ortiz, Mirella F; Figueiredo, Marcelo RA; Nissen, Scott J; Wersal, Ryan M; Ratajczyk, William A; Dayan, Franck E
Abstract: BACKGROUND: Hybrid watermilfoil is becoming more prevalent in many lakes where the invasive Eurasian ( Myriophyllum spicatum, EWM) and native northern watermilfoil ( M. sibiricum ) co‐occur. These Eurasian and northern watermilfoil hybrids (HWM) grow 30% faster and in many cases are less sensitive to 2, 4‐dichlorophenoxy acetic acid (2, 4‐D) than either parent. The mechanism(s) impacting 2, 4‐D tolerance in these hybrids was investigated by comparing the absorption, translocation, metabolism, and desorption of two 2, 4‐D formulations in EWM and HWM. RESULTS: 2, 4‐D absorption in EWM and HWM was 5.7 and 7.9 times the external herbicide concentration determined by the plant concentration factor, a metric used to determine herbicide bioaccumulation, and 2, 4‐D butoxyethyl ester absorption was 35.6 and 52.1 times the external concentration in EWM and HWM, respectively. Herbicide bioaccumulation was greater in HWM than in EWM. Herbicide translocation to HWM roots was limited at 192 HAT and herbicide desorption in HWM was slightly lower than EWM. No differences were found in herbicide metabolism between the two plant species. CONCLUSION: 2, 4‐D resistance in HWM is not due to non‐target‐site resistance as no differences in herbicide absorption, translocation, desorption and/or metabolism were identified; therefore, target‐site resistance is the most likely resistance mechanism. More research is needed to identify the molecular basis for the 2, 4‐D‐resistant trait in HWM. © 2021 Society of Chemical Industry. Abstract : Hybrid watermilfoil is becoming more prevalent in many lakes where the invasive and native watermilfoil co‐occur. These hybrids grow 30% faster and in many cases are becoming less sensitive to 2, 4‐D. The resistance is not due to NTSR as no differences in herbicide absorption, translocation, desorption and/or metabolism were identified.